A new genus and ten new species of jumping plant lice (Hemiptera: Triozidae) from Allocasuarina (Casuarinaceae) in Australia - Taylor, Gary S.; Jennings, John T.; Purcell, Matthew F.; Austin, Andy D. (Zootaxa, 2011)
Twelve species of jumping plant lice, Hemiptera: Psylloidea, in two genera are recognised from plants of the genus Allocasuarina (Casuarinaceae) in Australia. Aacanthocnema Tuthill & Taylor comprises two species that are here redescribed, Aa. casuarinae (Froggatt) and Aa. dobsoni (Froggatt), together with four new species, Aa. burckhardti Taylor, Aa. huegelianae Taylor, Aa. luehmannii Taylor, and Aa. torulosae Taylor. A new genus, Acanthocasuarina Taylor, comprises six new species: Ac. acutivalvis Taylor, Ac. campestris Taylor, Ac. diminutae Taylor, Ac. muellerianae Taylor, Ac. tasmanica Taylor, and Ac. verticillatae Taylor. Both genera are characterised by an elongate habitus, short Rs and short, triangular radial and cubital fore wing cells, ventrally produced genal processes beneath angular, overhanging apical margin of vertex, antennae short, and nymphs characteristically elongate, heavily sclerotised and scale-like. Species of Acanthocasuarina have rhinaria on antennal segments 4, 6, 8 and 9, the hind tibia has 1 outer and 2 inner spurs and the female proctiger has a posterior apical hook. In contrast, species of Aacanthocnema lack rhinaria on antennal segment 8 and sclerotised spurs on the hind tibia, and the female lacks a posterior apical hook on the proctiger. Trioza banksiae Froggatt stat. rev. is removed from Aacanthocnema. Keys to genera and species are provided, together with notes on their biology, host associations and biogeography.